Justificaciones médicas de la jornada laboral máxima de ocho horas. - Haro-García, Luis; Sánchez-Román, Raúl; Juárez-Pérez, Cuauhtémoc Arturo; Larios-Díaz, Enrique (Revista Medica del IMSS)
The eight-hour shift work is one of the main achievements of the organized workers. International solidarity with United States miners, who were massacred in Chicago at 1886 and the aftermath of the World War I, promoted the establishment of the eight-hour shift work in many countries. In Mexico, the 1917 Social Rights Declaration adhered to this position under the idea that the excessive workload above the 8-hour limit had negative effects on the health of workers; nevertheless, this statement seems to be sustained only by testimonies, anecdotic opinions and/or by the logic and common sense that then prevailed. For this reason, a literature review was carried out in search for the evidence supporting this apparently immovable length of the shift work. The globalization of the economy and the tendency towards flexibility and deregulation of current contractual relationships, are the new challenges that the eight-hour shift work is facing.